ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI PMA DI BATAM - Zainuddin, Muhammad (Universitas Negeri Semarang, 2009)
Investment plays an important role in the economic growth viewed both from development theory andpolicy perspectives. Strategic measures must be taken to increase the Foreign Direct Investment (FDI) toIndonesia amid the emergence of complicated investment problems and the downturn of investmentcompetitiveness. The research is aimed to analyze factors influencing investment decisions in in Batam.Secondary quantitative data are used to analyze the determinant factors of FDI in a certain industrialestate. Ordinary Least Square (OLS) method are employed and using panel data of 16 industrial areasduring 3 years (2005-2007). The dependent variable is FDI /investment plan. The Independent variablesare rental rate, maintenance fee, labor supply, export value and electricity. The result of regressionanalysis shows that the variable of maintenance fee, labor and export statistically influence the FDI inBatam. While variable of rental rate and electricity do not have significant effect.Keywords: Foreign Direct Investment, Industrial Estates, Investment plan